Prevalence of Autoimmune Thyroiditis and Other Autoimmune Diseases in Relation to Serum BAFF/APRIL Levels in Prolactinoma Patients - Özlem Kanburoğlu Meletli; Alev Altınova; Başak Bolayır; Resul Karakuş; Meriç Coşkun; Mehmet Muhittin Yalçın; Müjde Aktürk; İlhan Yetkin; Füsun Saadet Toruner (Gazi Medical Journal, 2024)
Objective: There may be an association between hyperprolactinemia and autoimmune diseases, possibly because of the immunostimulatory effect of prolactin. The aim of this study was to investigate the prevalence of thyroid and non-thyroid autoimmune diseases, serum B-cell activating factor (BAFF), and proliferation- inducing ligand (APRIL) levels as indicators of increased autoimmunity, quality of life, depression, and anxiety in patients with prolactinoma. Methods: Fifty-six premenopausal women with prolactinoma and 50 healthy premenopausal women were included in the study. Autoimmune markers, including anti-nuclear antibody, rheumatoid factor immunoglobulin M (IgM) (RF-IgM), anti-double-stranded DNA (anti-dsDNA), anti-transglutaminase IgA (anti TG-IgA), and anti-Sjogren’s syndrome A (anti-ssA), serum BAFF, APRIL and vitamin B12 levels, thyroid function tests, anti-thyroid peroxidase (anti-TPO), anti-thyroglobulin and thyroid Doppler ultrasound, were evaluated. Short-form 36, Beck Depression Inventory, and Beck Anxiety Inventory tests were also used. Results: The prevalence of autoimmune thyroiditis (AIT) was 32.1% in the patient group, whereas the prevalence of newly diagnosed AIT was similar to controls (p>0.05). Vitamin B12 deficiency was higher in patients with prolactinoma than in controls (25.6% and 9.1%, p=0.016). Autoantibody positivity was found to be similar between the groups (35.7% and 28.1%, p=0.25). Serum BAFF and APRIL levels were not different in patients with prolactinoma than in controls (p>0.05). Quality of life, anxiety, and depression scores were not different between patients with or without AIT and those with or without positivity for any autoantibody (p>0.05). Conclusion: One-third of the patients were diagnosed with AIT and one-fourth of the patients had vitamin B12 deficiency in our study. However, non-thyroid autoimmune diseases did not increase and no alterations were detected in serum BAFF/APRIL levels in patients with prolactinoma.